2019
DOI: 10.1007/s12273-019-0564-y
|View full text |Cite
|
Sign up to set email alerts
|

Urban weather modeling applications: A Vienna case study

Abstract: Recently, the interest in urban weather modeling methods has been steadily increasing. This is in part due to the insight that thermal building performance simulations are typically undertaken with standardized weather files that provide a rather general perspective on urban weather conditions. This may lead toward errors in conclusions drawn from modeling efforts. In this context, present contribution reports on the potential of different approaches to generate location-dependent urban meteorological data. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Several parameterization approaches (Kusaka et al 2001;Martilli et al 2002;Salamanca et al 2010) were developed to better represent cities and evaluated in a number of different case study regions (e.g. Salamanca et al 2011;Zhang et al 2011;Garcia-Diez et al 2016;Ronda et al 2017;Göndöcs et al 2017;Vuckovic et al 2020, Molnár et al 2019. However, mesoscale model simulations on a sub-kilometre spatial scale are computationally expensive and therefore hard to apply for weather forecasting purpose in operational mode.…”
Section: Introductionmentioning
confidence: 99%
“…Several parameterization approaches (Kusaka et al 2001;Martilli et al 2002;Salamanca et al 2010) were developed to better represent cities and evaluated in a number of different case study regions (e.g. Salamanca et al 2011;Zhang et al 2011;Garcia-Diez et al 2016;Ronda et al 2017;Göndöcs et al 2017;Vuckovic et al 2020, Molnár et al 2019. However, mesoscale model simulations on a sub-kilometre spatial scale are computationally expensive and therefore hard to apply for weather forecasting purpose in operational mode.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, LCZ mapping by means of WUDAPT L0 may deconstruct cities into distinct urban landscapes, based on a range of physical parameters [102], parameters that generate similar thermal signatures at a neighbourhood scale. To date, LCZ classification has been established by the WUDAPT method for many cities in western Europe [102,[105][106][107][108][109][110], in central Europe [102,109,[111][112][113][114][115][116][117][118][119], southern Europe [109,[120][121][122] and eastern Europe [123], as well as throughout Europe [124].…”
Section: Expert Knowledge-based Methodsmentioning
confidence: 99%
“…Some studies [119,120,122] have demonstrated that LCZ data can improve model performance by incorporating the LCZ scheme generated from WUDAPT L0 into the weather research forecasting (WRF) model, i.e., they have shown that the building effect parameterization-building energy model (BEP-BEM) is sensitive to landscape heterogeneity.…”
Section: Expert Knowledge-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations